2021
DOI: 10.1016/j.cjco.2021.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Ventricular-Arterial Stiffening on Exercise Hemodynamics in Adults With Repaired Coarctation of Aorta

Abstract: Background: Patients with coarctation of aorta (COA) have arterial stiffening, and this is associated with impaired cardiac reserve and hypertensive systolic blood pressure (SBP) response during exercise. However, whether patients with COA have concomitant left ventricular (LV) stiffening and the potential impact of combined ventricular-arterial stiffening on exercise hemodynamics are unknown. Methods: We studied 174 patients with repaired COA (aged 39 AE 11 years and male 103 [59%]) and 174 matched controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…An aortic or mitral valve prosthesis was present in 4 patients (20%) each (coexistent in 1). Ascending to descending aorta peak and mean gradients were 19 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and 13 (7-18) mmHg, respectively. The mean ratio of diameters between the aortic isthmus and the descending thoracic aorta at the diaphragm measured by crosssectional imaging was 0.8 ± 0.2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An aortic or mitral valve prosthesis was present in 4 patients (20%) each (coexistent in 1). Ascending to descending aorta peak and mean gradients were 19 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and 13 (7-18) mmHg, respectively. The mean ratio of diameters between the aortic isthmus and the descending thoracic aorta at the diaphragm measured by crosssectional imaging was 0.8 ± 0.2.…”
Section: Resultsmentioning
confidence: 99%
“…Four patients (20%) were in New York Heart Association functional class III-IV, while 4 were asymptomatic. Nine patients had pre-procedural outpatient upper and lower limb blood pressure measured; median systolic pressure gradient was 25 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) mmHg. Detailed information of pre-procedural imaging is depicted in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulse-wave velocity was higher in patients who were hypertensive either on ABPM or during exercise [30]. Egbe et al [31] studied the effect of ventricular and arterial stiffening on exercise response and found that patients with combined ventricular-vascular stiffening had impaired output response and hypertensive response during exercise demonstrating the hemodynamic importance. The utility of exercise testing in management of coarctation patients needs further clinical validation but could be highly relevant to better identify patients at risk for developing long-term complications.…”
Section: Vascular Properties and Ventricular-vascular Interactionsmentioning
confidence: 99%